Methodology for Developing Students' Creative Thinking through Studying Nature Depictions in Literature Lessons (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Every student should be able to understand the duality of nature and man. Because in the duality of man and the universe, preserving nature and knowing the factors that cause the deterioration of the ecological state of our Mother Earth are reflected in understanding the unity of the universe and man. A student who understands the universe can take its uniqueness to heart. Taking these into account, it will be possible to develop their irrational thinking by asking students what they understand by the duality of man and the universe.